2019
DOI: 10.1590/rbz4820180023
|View full text |Cite
|
Sign up to set email alerts
|

Typology of dairy production systems that meet Brazilian standards for milk quality

Abstract: Animal production systems and agribusiness Full-length research article Typology of dairy production systems that meet Brazilian standards for milk quality ABSTRACT-We aimed to compare the typology of dairy production systems (DPS) that meet Brazilian quality standards with that of non-compliant DPS. Semi-structured questionnaires were applied in 128 DPS located in Santa Izabel do Oeste, Paraná, Brazil (25°49'16" S and 53°29'04" W). In addition, milk quality reports of each DPS were analyzed. Dairy production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
(28 reference statements)
0
18
0
7
Order By: Relevance
“…Difficulty in complying with institutional requirements such as those set by Normative Instructions (NI) nos. 51, 62, 76, and 77 is another factor that negatively affects the performance of dairy producers (Defante, Damasceno, Bánkuti, & Ramos, 2019). NI 76 and 77 repealed previous NI 51 and 62, defining new rules for the production, storage, transport, and quality of milk in Brazil (Instrução Normativa n. 62, 2011;Instrução Normativa n. 31, 2018;Instrução Normativa n. 76, 2018;Instrução Normativa n. 77, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulty in complying with institutional requirements such as those set by Normative Instructions (NI) nos. 51, 62, 76, and 77 is another factor that negatively affects the performance of dairy producers (Defante, Damasceno, Bánkuti, & Ramos, 2019). NI 76 and 77 repealed previous NI 51 and 62, defining new rules for the production, storage, transport, and quality of milk in Brazil (Instrução Normativa n. 62, 2011;Instrução Normativa n. 31, 2018;Instrução Normativa n. 76, 2018;Instrução Normativa n. 77, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Processing industries dominate the sector, and less power is held by dairy farms. Moreover, misalignment between production characteristics of dairy farms and institutional and market demands contributes to this scenario (Brito et al, 2015b;Defante et al, 2019;Fernandez-Stark, Bamber, & Gereffi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…All SDS, irrespective of their classification into the clusters, can be defined as smallholders' systems. Defante et al (2019) observed that only 6.3% of dairy systems in Paraná, Brazil, reached the minimum quality standards for milk traits and pointed out that smallholders face expressive difficulty in meeting the milk quality normatives.…”
Section: Discussionmentioning
confidence: 99%
“…Improving milk quality; on the contrary, does not require major investment because they are closely associated with nutritional and hygienic-sanitary management (KUNDA et al, 2015;KAMANA et al, 2016). Dairy production systems that comply with quality regulations have higher productivity and better bargaining power with the industry for the marketing of milk (DEFANTE et al, 2019). In addition, non-conformity with quality regulations prompts dairy producers to operate in the informal market or even abandon the activity (SOUZA & BUAINAIN, 2013).…”
Section: Microbiologymentioning
confidence: 99%